The Protective Effects of the Supercritical-Carbon Dioxide Fluid Extract of Chrysanthemum indicum against Lipopolysaccharide-Induced Acute Lung Injury in Mice via Modulating Toll-Like Receptor 4 Signaling Pathway. (25th August 2014) - Wu, Xiao-Li; Feng, Xue-Xuan; Li, Chu-Wen; Zhang, Xiao-Jun; Chen, Zhi-Wei; Chen, Jian-Nan; Lai, Xiao-Ping; Zhang, Sai-Xia; Li, Yu-Cui; Su, Zi-Ren
Abstract : The supercritical-carbon dioxide fluid extract of Chrysanthemum indicum Linné. (CFE) has been demonstrated to be effective in suppressing inflammation. The aim of this study is to investigate the preventive action and underlying mechanisms of CFE on acute lung injury (ALI) induced by lipopolysaccharide (LPS) in mice. ALI was induced by intratracheal instillation of LPS into lung, and dexamethasone was used as a positive control. Results revealed that pretreatment with CFE abated LPS-induced lung histopathologic changes, reduced the wet/dry ratio and proinflammatory cytokines productions (TNF- α, IL-1 β, and IL-6), inhibited inflammatory cells migrations and protein leakages, suppressed the levels of MPO and MDA, and upregulated the abilities of antioxidative enzymes (SOD, CAT, and GPx). Furthermore, the pretreatment with CFE downregulated the activations of NF- κ B and the expressions of TLR4/MyD88. These results suggested that CFE exerted potential protective effects against LPS-induced ALI in mice and was a potential therapeutic drug for ALI. Its mechanisms were at least partially associated with the modulations of TLR4 signaling pathways.